Eksplorasi Etos Kerja Generasi Z dalam Lingkungan Kerja Hybrid: Studi Kualitatif pada Perusahaan Multinasional - Fajar Aulia (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
The transformation of work structures due to the rapid adoption of hybrid models post-COVID-19 has brought significant changes to how Generation Z constructs and interprets work ethics. As a digitally native cohort, Generation Z highly values flexibility, autonomy, and meaningful engagement, which pose distinct implications for multinational companies aiming to remain competitive in a globalized work environment. This study adopts a qualitative exploratory case study approach to examine how Generation Z employees develop and demonstrate work ethics in hybrid work systems. Twelve participants, selected purposively based on their experience of working in hybrid settings for a minimum of one year, participated in semi-structured in-depth interviews. Thematic analysis was conducted following Braun and Clarke’s framework. Findings reveal that Generation Z perceives work ethic as a function of personal responsibility, digital proficiency, and performance-based autonomy. Participants emphasized trust, transparent communication, and collaborative digital tools as essential to maintaining commitment and discipline. However, they also acknowledged challenges in delineating work-life boundaries, leading to role ambiguity and stress. The study concludes that to foster sustainable work ethics, multinational organizations must adopt flexible yet structured management strategies that align with Generation Z’s values while ensuring accountability. These insights contribute to evolving HR practices in managing digital-era workforce complexities.